Nutrient and temperature constraints on primary production and net phytoplankton growth in a tropical ecosystem. Issue 7 (12th June 2021) - López‐Sandoval, Daffne C.; Duarte, Carlos M.; Agustí, Susana
Abstract: The Red Sea depicts a north–south gradient of positively correlated temperature and nutrient concentration. Despite its overall oligotrophic characteristics, primary production rates in the Red Sea vary considerably. In this study, based on five cruises and a 2‐year time series (2016–2018) sampling in the Central Red Sea, we determined phytoplankton photosynthetic rates (PP) by using 13 C as a tracer and derived phytoplankton net growth rates ( μ ) and chlorophyll a (Chl a )‐normalized photosynthesis (P B ). Our results indicate a ninefold variation (14–125 mgC m −2 h −1 ) in depth‐integrated primary production and reveal a marked seasonality in PP, P B, and μ . Depth‐integrated PP remained <30 mg C m −2 h −1 during spring and summer, and peaked in autumn–winter, particularly in the southernmost stations ( 17°N). In surface waters, phytoplankton grew at a slow rate (0.2 ± 0.02 d −1 ), with the population doubling every 3.5 days, on average. However, during the autumn–winter period, when Chl a concentrations peaked in the central and southern regions, μ increased to values between 0.60 and 0.84 d −1, while P B reached its maximum rate (7.8 mgC [mg Chl a ] −1 h −1 ). We used path analysis to resolve direct vs. indirect components between correlations. Our results show that nutrient availability modulates the photosynthetic performance and growth of phytoplankton communities and that P B and μ fluctuations are not directly associated with temperature changes. Our study suggests that similarly to other oligotrophic warm seas, phosphorus concentration exerts a key role in defining photosynthetic rates and the biomass levels of phytoplankton communities in the region.